Herpecaudin from Herpetospermum caudigerum, a Xanthine Oxidase Inhibitor with a Novel Isoprenoid Scaffold - Jiang, He Zhong; Tan, Rui; Jiao, Rui Hua; Deng, Xin Zhao; Tan, Ren Xiang (Planta Medica, 2016)
Herpecaudin (3), a xanthine oxidase inhibitor with an unprecedented scaffold, was discovered from Herpetospermum caudigerum seeds. The structure was determined by spectroscopic and X-ray single crystallographic methods. A possible biogenetic pathway leading to herpecaudin is proposed, starting from congeners 23,24-dihydrocucurbitacin E (1) and endecaphyllacin B (2), and involving retro-aldol cleavage as a key step. All three compounds proved to be active and represent new scaffolds of non-purine analogue xanthine oxidase inhibitors.
Keywords: Herpetospermum caudigerum; Cucurbitaceae; Herpecaudin; xanthine oxidase inhibitor; retro-aldol reaction; cucurbitane-type terpenoid